2018
DOI: 10.1155/2018/4318678
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and Health Professionals’ Experiences of Using Virtual Reality Technology for Upper Limb Training after Stroke: A Qualitative Substudy

Abstract: Background In recent years, virtual reality (VR) therapy systems for upper limb training after stroke have been increasingly used in clinical practice. Therapy systems employing VR technology can enhance the intensity of training and can also boost patients' motivation by adding a playful element to therapy. However, reports on user experiences are still scarce. Methods A qualitative investigation of patients' and therapists' perspectives on VR upper limb training. Semistructured face-to-face interviews were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 24 publications
2
51
0
Order By: Relevance
“…The most important finding of the study might be that walking with VR was an enjoyable experience. Similar to previous research [24] participants described the experience as entertaining, exciting, challenging, and enjoyable. Although, experiences of training to walk with VR are scarcely investigated, a recent study [25] showed that patients preferred walking with, rather than without VR.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The most important finding of the study might be that walking with VR was an enjoyable experience. Similar to previous research [24] participants described the experience as entertaining, exciting, challenging, and enjoyable. Although, experiences of training to walk with VR are scarcely investigated, a recent study [25] showed that patients preferred walking with, rather than without VR.…”
Section: Discussionsupporting
confidence: 76%
“…In contrast to previous research [17, 24, 28] the VR system in this study did not include a dimension of competitiveness as it was not designed to be a game. However, in addition to the continuous visual and auditory feedback given during walking, participants could compete with themselves in terms of walking speed and endurance, which was also emphasized by some participants.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This could be considered a limitation since one large focus group with all six clinicians may have facilitated deeper exploration of ideas and opinions with others (Folch-Lyon & Trost, 1981). Despite our relatively small sample size (albeit in line with sample sizes of similar studies; Lane et al, 2019;Ogourtsova et al, 2019;Pallesen et al, 2018;Niraji, Wright & Powell, 2018), we were able to collect the personal perspectives of various end-users (stroke survivors with and without spatial neglect, carers of different ages and multidisciplinary stroke clinicians).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the impact of virtual environments is relevant as an initial approach for an individual’s actual exposure in the real-life context. It is an opportunity to train individuals in a secure environment, with a corrective factor performed according to the options chosen by the therapist: The intensity of emotions and the type of environment and avatars can be manipulated (Pallesen, Andersen, Hansen, Lundquist, & Brunner, 2018). The combination of these three variables will enable the therapist to customize a wide range of difficulty levels involved in rehabilitation.…”
Section: Discussionmentioning
confidence: 99%